Improving emergency department care for adults presenting with mental illness: a systematic review of strategies and their impact on outcomes, experience, and performance - Austin, Elizabeth E.; Cheek, Colleen; Richardson, Lieke; Testa, Luke; Dominello, Amanda; Long, Janet C.; Carrigan, Ann; Ellis, Louise A.; Norman, Alicia; Murphy, Margaret; Smith, Kylie; Gillies, Donna; et al. (Frontiers in Psychiatry, 2024)
Background: Care delivery for the increasing number of people presenting at hospital Emergency Departments (ED) with mental illness is a challenging issue. This review aimed to synthesise the research evidence associated with strategies used to improve ED care delivery outcomes, experience, and performance for adults presenting with mental illness.We systematically reviewed the evidence regarding the effects of ED-based interventions for mental illness on patient outcomes, patient experience, and system performance, using a comprehensive search strategy designed to identify published empirical studies. Systematic searches in Scopus, Ovid Embase, CINAHL and Medline were conducted in September 2023 (from inception; review protocol prospectively registered in Prospero CRD42023466062). Eligibility criteria were: (1)primary research study, published in English; and (2)reported a)an implemented model of care or system change within the hospital ED context, b)focused on adult mental illness presentations, and c)evaluated system performance, patient outcomes, patient experience, or staff experience. Pairs of reviewers independently assessed study titles, abstracts and full texts according to pre-established inclusion criteria with discrepancies resolved by a third reviewer. Independent reviewers extracted data from the included papers using Covidence ( 2023) and the quality of included studies was assessed using the Joanna Briggs Institute suite of critical appraisal tools.A narrative synthesis was performed on the included 46 studies, comprising pre-post (n=23), quasi-experimental (n=6), descriptive (n=6), RCTs (n=3), cohort (n=2), cross-sectional (n=2), qualitative (n=2), realist evaluations (n=1), and time series analysis studies (n=1). Eleven articles focused on presentations related to substance use disorder presentation, nine focused on suicide and deliberate self-harm presentations, and 26 reported mental illness presentations in general. Strategies included models of care, decision support tools, discharge and transfer refinements, adjustments to liaison psychiatry services, telepsychiatry, and care standardisations. System performance measures were reported in 33 studies (72%), with fewer studies reporting measures of patient outcomes (n=19,41%), patient experience (n=10,22%), or staff experience (n=14,30%). Few interventions reported outcomes across all four domains. Heterogeneity in study samples, strategies and evaluated outcomes makes adopting existing strategies challenging.Care for mental illness is complex, particularly in the emergency setting. Strategies to provide care must align ED system goals with patient goals and staff experience.